2019
DOI: 10.1177/0013916518781197
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Crime Revisited: An Exploration of Monthly Temperature Anomalies and UCR Crime Data

Abstract: A growing body of research suggests a positive connection between climate change and crime, but few studies have explored the seasonal nature of that link. Here, we examine how the impact of climate change on crime may partly depend on specific times of the year as recent climatological research suggests that climate change may have a diverging impact during different times of the year. To do so, we utilize the largest, most current dataset of all main categories of reported crime by month and year in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…A typical solution to serial dependence—inclusion of lagged dependent variables—is not appropriate for Poisson and negative binomial modeling. Although many variations of time-series modeling for count data have been developed in recent years, the literature remains favorable to GLMs with added binary variables to control for level shifts in specific time units (Mares & Moffett, forthcoming). Such controls when implemented appropriately can remove most—if not all—time dependence, especially if the source of serial correlation is structural in nature (Cameron & Trivedi, 2013).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…A typical solution to serial dependence—inclusion of lagged dependent variables—is not appropriate for Poisson and negative binomial modeling. Although many variations of time-series modeling for count data have been developed in recent years, the literature remains favorable to GLMs with added binary variables to control for level shifts in specific time units (Mares & Moffett, forthcoming). Such controls when implemented appropriately can remove most—if not all—time dependence, especially if the source of serial correlation is structural in nature (Cameron & Trivedi, 2013).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…In 2019, India witnessed high temperature secondlongest period in the last 31 years between March 7 and June 2. Long heat waves swept through 23 states which killed almost 300 people in India 19 .…”
Section: Global Warmingmentioning
confidence: 99%
“…However, all previous estimates are either back-of-the-envelope or do not account for crucial regional (within a single nation) and seasonal dependencies recently discovered in the relationship between criminal activity and temperature (Hsiang et al 2013, Ranson, 2014, Hsiang et al 2017, Mares and Moffett, 2019. We established a methodology that allows for known regional (Mares and Moffett 2016, de Melo et al 2018, Linning et al 2017, Mares and Moffett 2019 and seasonal variations (Cohn and Rotton, 2000, McDowall et al 2012, Carbone-Lopez and Lauritsen 2013, McDowall and Curtis, 2015 to be detected and built into the statistical models developed (Harp and Karnauskas 2018). In particular, stronger relationships between temperature and both violent and property crime during wintertime months provided strong evidence for the routine activities theory as the main driver of the crime-temperature relationship.…”
Section: Motivationmentioning
confidence: 99%
“…The spatial variation of multi-model mean projections of surface air temperature is considerable, even across the continental US (figure 1(a) uses RCP8.5 forcing and the end-of-century period for an illustrative example). In addition, as noted previously, the quantitative sensitivity of violent crime to temperature also varies spatially (Harp andKarnauskas 2018, Mares andMoffett 2019). To enable the calculation of appropriate region-based projections, we adopted the optimal boundaries previously determined in our retrospective study, also identified in figure 1(a).…”
Section: Building Empirical Modelsmentioning
confidence: 99%
See 1 more Smart Citation